Correlation of Chimerism with Acute Graft-versus-Host Disease in Rats following Liver Transplantation - Fei Xue; Wei Chen; Xue-Li Bai; Guo-Dong Xu; Liang Liang; Ting-Bo Liang (International Journal of Hepatology)
The accurate diagnosis of acute graft-versus-host disease following liver transplantation (LTx-aGVHD) has been hampered. Chimerism appears in the majority of recipients after LT and its significance in the diagnosis of LTx-aGVHD has not been clearly established. To demonstrate the significance of chimerism on the diagnosis of LTx-aGVHD, we compared the change of chimerism in syngeneic LT recipients, semiallogeneic LT recipients, and LTx-aGVHD induced recipients. Chimerism in PBMCs following sex-mismatched LT was identified by real-time PCR based on a rat Y-chromosome-specific primer. All recipients in semiallogeneic group grew in a normal pattern. However, when 4×108 donor splenocytes were transferred simultaneously during LT, the morbidity of lethal aGVHD was 100%. The chimerism appeared slightly higher in the semiallogeneic group than in the syngeneic LT group, but the difference was not significant. However, when the recipients developed lethal aGVHD after LT, chimerism in the PBMCs increased progressively, and even at an early time, a significant increase in chimerism was observed. In conclusion, high level chimerism correlated well with LTx-aGVHD, and detection of chimerism soon after transplantation may be of value in the diagnosis of LTx-aGVHD prior to the onset of symptoms.